Traumatic Inhalation due to Merapi Volcanic Ash - Ika Trisnawati; Eko Budiono; Sumardi Sumardi; Andang Setiadi (Interna Publishing, 2016)
Pneumonoultramicroscopicsilicovolcanoconiosis is fibrotic lung diseases of the pulmonary parenchyma following chronic inhalation of inorganic dusts containing crystalline silicon dioxide. The acute manifestations observed after heavy ashfalls include attacks of asthma and bronchitis, with an increased reporting of cough, breathlessness, chest tightness, and wheezing due to irritation of the lining of the airways. The chronic health condition of most concern is silicosis, a diffuse nodular fibrosis of the lungs, develops slowly, usually appearing 10 to 30 years after first exposure. A 35 years old male was admitted to Sardjito Hospital, Yogyakarta with complaints of progressive dyspnoea, right side chest pain since last 3 month and periodic episodes of dry cough. He had history of exposure to volcanic ash at the location around volcano eruption for about 10 month. Examination revealed hyperresonant note, diminished vesicular breath sounds in lower right side of the chest. The chest X-ray presence leads to bleb. Based on the clinical and radiological suspicion of pneumoconiosis the patient was submitted to computed tomography of the chest and revealed bilateral multiple bullae mainly at the right lung field. The biopsy specimen verified the diagnosis of anthrocosilicosis. There is no proven specific therapy for any form of silicosis. Symptomatic therapy should include treatment of airflow limitation with bronchodilators, aggressive management of respiratory tract infection with antibiotics, and use of supplemental oxygen (if indicated) toprevent complications of chronic hypoxemia. Key words: Pneumonoultramicroscopicsilicovolcanoconiosis, inorganic particles inhalation, dyspnoea, bullae.